Psychological contract on employee consequences among collegiate head coaches: The moderating role of procedural justice - Won, D.; Chiu, W.; Bravo, G. A. (International Journal of Sports Science & Coaching, 2023)
The current study investigated the relationship between the psychological contract (PC), trust, perceived organizational support (POS), organizational commitment, and turnover intention among collegiate head coaches. In addition, this study explored the moderating effect of procedural justice on the relationship between these variables. Data were collected from 283 full-time head coaches in the NCAA and were primarily analyzed using PLS-SEM. The results indicated that relational PC (R-PC), compared to transactional PC (T-PC), was more influential in affecting coaches` POS, trust, and commitment, while T-PC influenced POS only, but not trust and commitment. In addition, both trust and POS were positively associated with coaches` affective commitment, while affective commitment, POS, and trust, in this order, were negatively related to their turnover intentions. Coaches` perceived procedural justice moderated the relationship between T-PC and employee consequences, indicating that T-PC was more meaningful in high justice situations.